(untitled) (Academia Science Repository, 2023)
181 documents were obtained in the general search; after eliminating duplicates and applying certain inclusion and exclusion criteria, 76 papers were used for this review. This study provides three main conclusions(Stevens and Bamber 2017; Uhrenholdt Madsen et al. 2020): During the period 1995-2023, academic interest in this topic has increased and the keywords ISO 45001, policy, occupational health and safety, management system, human; a list of authors who have conducted scientific work on the basis of ISO 45001 is compiled; and the top 10 countries that conducted scientific work based on ISO 45001 are presented based on geographical analysis. VOS viewer software was used to investigate the bibliometric research method and bibliographic display map. There are three phases to the bibliometric research process, they are search criteria and source identification, software and data extraction, and then data analysis and interpretation. To our knowledge, no bibliometric comparative reviews of ISO 45001 have been published. This research will serve as a foundation for future research(Maksymiuk 2000).